IMPLEMENTASI KURIKULUM 2013 pada MATA PELAJARAN IPS KELAS VIII di SMP SEKECAMATAN GUNUNGPATI - Nurmeipan, Reza; Hermanto, Fredy (Program Studi Pendidikan IPS UNNES, 2020)
The teacher has a role in implementing the 2013 curriculum in social studies lessons in directing students to be active during learning. This study aims to determine the implementation of the 2013 curriculum in social science education class VIII in Junior High School, Gunungpati District, seen from the planning, implementation, evaluation development, supporting factors and inhibiting factors. The research method used is a qualitative method. The results showed that (1) the preparation of lesson plans that the teacher uses in the form of syllabus and lesson plans refers to the standard process. (2) The teacher implementation process uses the group discussion method and the scientific approach with a learning model according to the 2013 curriculum. (3) the evaluation of teacher learning designs an assessment instrument to assess the abilities of students in the realms of attitudes, knowledge and skills. (4) supporting factors include MGMP training which discusses learning tools, implementation and evaluation techniques. The inhibiting factor for teachers is still difficult to developtype learning HOTS in the realm of skills. Guru memiliki peran mengimplementasikan kurikulum 2013 pada pelajaran IPS mengarahkan peserta didik untuk aktif saat pembelajaran. Penelitian ini bertujuan untuk mengetahui implementasi kurikulum 2013 pada mata pelajaran IPS kelas VIII di SMP Sekecamatan Gunungpati dilihat dari penyusunan perencanaan, pelaksanaan, pengembangan evaluasi, faktor pendukung serta faktor penghambat. Metode penelitian yang digunakan adalah metode kualitatif. Hasil penelitian menunjukkan bahwa (1) penyusunan perencanaan pembelajaran yang guru gunakan dalam bentuk silabus dan RPP mengacu pada standar proses. (2) proses pelaksanaan guru menggunakan metode diskusi kelompok dan pendekatan saintifik dengan model pembelajaran sesuai kurikulum 2013. (3) evaluasi pembelajaran guru merancang instrumen penilaian untuk menilai kemampuan peserta didik mencangkup ranah sikap, pengetahuan dan keterampilan. (4) faktor pendukung mengikutsertakan pelatihan MGMP membahas perangkatan pembelajaran, pelaksanaan dan teknik evaluaasi. Faktor penghambat guru masih sulit mengembangkan pembelajaran tipe HOTS pada ranah keterampilan.